ANALYZING IMPACT OF ESG PRINCIPLES ON PERFORMANCE: A PERSPECTIVE FROM SUSTAINABILITY BALANCED SCORECARD - Anis, Idrianita; Avrilia, Vera (Jurnal Akuntansi dan Keuangan Indonesia, 2024)
The diverse findings regarding the effects of Environmental, Social, and Governance (ESG) principles on performance are prompting the examination of these practices using Sustainability Balanced Scorecard (SBSC) as a Strategic Performance Measurement System (SPMS). Therefore, this study aimed to construct ESG principles model and index by analyzing content from annual and sustainability reports which served as indicators for governance maturity level. ESG principles were further categorized within the Triple I framework, consisting of Sustainability Intention, Integration, and Implementation. The study also used purposive sampling focusing on the best companies using ESG principles in the non-financial sector listed on the Indonesia Stock Exchange including the SRI KEHATI and LQ45 Index from 2017 to 2021 (212 Observations). The findings showed that ESG measures did not impact profitability but positively affect the organization's value. This discovery suggested a dynamic endogeneity, necessitating future exploration of investment efficiency over a minimum of ten years to comprise sustainability and governance adaptation across non-financial sectors in Indonesia and cross-border countries.